PENGEMBANGAN MEDIA AJAR POWER POINT BERBASIS HYPERLINK DENGAN MODEL PBL UNTUK MENINGKATKAN KEMAMPUAN MENYIMAK SISWA KELAS III SD - Mutaqin, Muhamad Zainal; Zaenuri, Zaenuri; Arbarini, Mintarsih (Attadib: Journal of Elementary Education, 2023)
One of the most fundamental skills in learning that children must possess is listening, and the same goes for media. Media plays a crucial role in the success of a child's learning in the classroom. This research aims to analyze the process of developing a product, test the feasibility and effectiveness of a developed instructional media product based on Hyperlink PowerPoint with a Project-Based Learning (PBL) model to enhance the listening skills of third-grade elementary school students. This study follows the 4D research and development model, consisting of four stages: Define, Design, Develop, and Disseminate. The research subjects include 32 students, and data collection methods involve observation, interviews, tests, questionnaires, expert validation, and documentation. Expert validation is employed to assess the feasibility of the developed Hyperlink PowerPoint instructional media.Based on the results of this research, the expert media validation trial obtained a score of 89%, material expert validation scored 89%, teacher response to the product was 86%, and student response to the media was 92%. The effectiveness test of the Hyperlink PowerPoint media can be evidenced by an increase in the percentage of students' pretest and posttest scores by 61% and is supported by an N-gain value of 0.69.